2013
DOI: 10.1002/qre.1503
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-Based r -plot for Evaluating Supersaturated Designs

Abstract: Orthogonality or near-orthogonality is an important property in the design of experiments. Supersaturated designs are natural when we wish to investigate the main effects for a large number of factors but are restricted to a small number of runs. These supersaturated designs, by definition, cannot satisfy pairwise orthogonality of all the factor columns in the design matrix. Hence, we need a means to evaluate the degree of near-orthogonality of different alternative supersaturated designs. It is usual to use n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This approach is only sensible if we believe in effect sparsity, which suggests that many of the factors will not be active, but we do not know a priori which these will be. Jang et al suggested correlation‐based r‐plot for evaluating supersaturated designs. This r‐plot is a checker plot in which off‐diagonal panels consist of boxes to show | r ij | = | corr ( c i , c j )|, which is the absolute value of the correlation coefficient between the ( i , j )th pair of design columns c i and c j .…”
Section: Graphical Methods For Evaluating Covering Arraymentioning
confidence: 99%
“…This approach is only sensible if we believe in effect sparsity, which suggests that many of the factors will not be active, but we do not know a priori which these will be. Jang et al suggested correlation‐based r‐plot for evaluating supersaturated designs. This r‐plot is a checker plot in which off‐diagonal panels consist of boxes to show | r ij | = | corr ( c i , c j )|, which is the absolute value of the correlation coefficient between the ( i , j )th pair of design columns c i and c j .…”
Section: Graphical Methods For Evaluating Covering Arraymentioning
confidence: 99%
“…Jang et al investigated the property of supersaturated design for comparative purposes. They checked the imbalance of number of levels for each column of arrays and called this a property of balance as orthogonality of strength 1.…”
Section: Criteria For Evaluating Covering Arraysmentioning
confidence: 99%